Effects of orientation, stress and exposure time on short intergranular stress corrosion crack behaviour in sensitised type 304 austenitic stainless steel - Rahimi, S; Marrow, T (2012)
Intergranular stress corrosion cracking (IGSCC) in austenitic stainless steels occurs at susceptible grain boundaries after sensitisation. In this study, the effects of test duration, static stress (applied and residual) and microstructure orientation on the developed populations of short crack nuclei are reported for a sensitised type 304 austenitic stainless steel in an acidified potassium tetrathionate (K 2S 4O 6) solution. The crack populations were analysed using the Gumbel distribution method, showing an increase in the characteristic crack lengths with increasing time and grain size. There is a weak, but measurable effect of stress on crack length. Tensile stress increases crack growth and compressive residual stresses introduced by surface machining are shown to be beneficial. A significant dependence on sample orientation is observed and this cannot be explained in terms of the bulk microstructure properties or characteristics, which showed no significant variations. © 2011 Blackwell Publishing Ltd.